2004
DOI: 10.1099/mic.0.26470-0
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of heat-shock-denatured, endogenous proteins and distribution of the IbpA/B and Fda marker-proteins in Escherichia coli WT and grpE280 cells

Abstract: Submission of wild-type Escherichia coli to heat shock causes an aggregation of cellular proteins. The aggregates (S fraction) are separable from membrane fractions by ultracentrifugation in a sucrose density gradient. In contrast, no protein aggregation was detectable in an E. coli grpE280 mutant either by this technique or by electron microscopy. In search of an explanation for this observation at a molecular level, two kinds of marker proteins were used: Fda (fructose-1,6-biphosphate aldolase), the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
0
22
1
Order By: Relevance
“…To this end, the endogenous ibpA was replaced by a chromosomal gene fusion to the yellow fluorescent protein (YFP) in the MG1655 sequenced wild-type E. coli strain. IbpA was previously shown to be present in the insoluble cellular fraction of heat-stressed cells (20). To check whether IbpA-YFP can serve as detector for protein aggregates, we exposed the strain expressing the fluorescent gene construct (MGAY) to various aggregating conditions.…”
Section: Reporting Inclusion Bodies In Vivo Inmentioning
confidence: 99%
“…To this end, the endogenous ibpA was replaced by a chromosomal gene fusion to the yellow fluorescent protein (YFP) in the MG1655 sequenced wild-type E. coli strain. IbpA was previously shown to be present in the insoluble cellular fraction of heat-stressed cells (20). To check whether IbpA-YFP can serve as detector for protein aggregates, we exposed the strain expressing the fluorescent gene construct (MGAY) to various aggregating conditions.…”
Section: Reporting Inclusion Bodies In Vivo Inmentioning
confidence: 99%
“…5B). We found that the outer membrane fraction of SecE-depleted cells was contaminated with aggregates that can cosediment with outer membranes during density gradient centrifugation (35,39). The spots corresponding to aggregated proteins were identified and removed from the analysis set as described in Materials and Methods (see Table S3 and Fig.…”
Section: Vol 190 2008 Characterization Of E Coli Cells Depleted Ofmentioning
confidence: 99%
“…Spot quantities were normalized using the "total intensity of valid spots" method to compensate for non-expression-related variations in spot quantities between gels (there were no significant variations in the total spot quantity between the two groups [SecE depletion and control]). Since protein aggregates can cosediment with outer membranes during density gradient centrifugation, an additional normalization step was required for analysis of the outer membrane gels (35,39). First, to distinguish between outer membrane FIG.…”
Section: Dementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lack of any obvious transmembrane domain or Sec-dependent signal peptide, ␣-Hsp associations with membranes have been well documented (2). E. coli IbpA/B localized in the outer membrane and functioned in protecting cells from heat and oxidative stress (51)(52)(53). M. tuberculosis Hsp16.3, a major immunodominant protein, was found to be a major membrane protein (54).…”
Section: Discussionmentioning
confidence: 99%